Failure Mode and Effect Analysis on the Impact of Zakat on the Local Economy - Darmawan, Darmawan; Alfajriyani, Siti (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
Purpose: This study employs a risk management approach to analyze factors influencing the impact of zakat on the local economy, with a focus on stimulating economic activity and job creation.Design/methodology: Data were collected from respondents involved in failure risk assessments based on frequency, impact, and detection capabilities of zakat institutions. Dominant factors were categorized into the collection, management, and utilization of zakat funds. The Failure Mode and Effect Analysis (FMEA) method was used to identify high-risk dominant factors.Findings: The study reveals critical factors that need immediate improvement, including trust, transparency, social campaigns, accountability, responsibility, forecasting, capital provision, planning, organizing, and training.Practical implications: This research highlights the need for zakat institutions to address key reflective indicators such as trust, transparency, social campaigns, accountability, responsibility, forecasting, capital provision, planning, organizing, and training to enhance the effectiveness of zakat in local economic development.Originality/Value: This study applies the FMEA method in the context of zakat management, providing a novel approach to identifying and prioritizing critical risk factors for improving the impact of zakat on local economies.